Nurse View on Improving Occupational Safety and Health in the Hospital Environment - Sefinez Muzena; Ozvitruk Mitoulaf (Inovasi Analisis Data, 2024)
Objective: This study aimed to identify the specific risks experienced by nurses, the safety measures in place and how they perceived its effectiveness at preventing falls from taking place which helped to identify areas for improvement when enhancing healthcare workers welfare. Methods: A structured questionnaire was administered to collect data on socio-demographics, specific sector employment types, safety practices and occupational risks. Trends were explored using percent distributions, means and chi-squared tests for independence where appropriate.Findings: The study found that OHS conditions in a University teaching hospital are noticeably different from a private hospital. Nurses in private sector hospitals had better working conditions also with the improved safety standards, comprehensive safety training and ergonomic design which was accredited by JCI. On the other side hospital nurses encountered poor safety leads, ergonomic deficiencies, and high rates of occupational diseases and injuries. University hospitals had more psychological stress, burnout, and job dissatisfaction than private hospitals; however, in terms of infection control they fared better compared to private hospitals who, although carrying out consistent monitoring programmes for PPE, were hindered with shift fatigue and stress.Novelty: This study offers a comparison of OHS conditions for nurses in private and public health care facilities and highlights the potential role of international accreditation for safer working environments. This has shone light on a long-neglected safety issue in academic hospitals.Research Implications: The study findings are expected to help policy amendments, labor protection policies for civil servants in university hospitals, NABH accreditation processes and monitoring of safety training and ergonomic improvements in both private sector hospital environments and public healthcare establishments.